Intrauterine growth restriction in monochorionic-diamniotic twins - Machado,Rita de Cássia Alam (2014)
Objective: to evaluate neonatal morbidity and mortality in monochorionic- -diamniotic (MCDA) twin pregnancies complicated by selective intrauterine growth restriction (sIUGR) and non-selective intrauterine growth resctriction (nsIUGR). Methods: neonatal morbidity parameters and mortality were analyzed in 34 twins with IUGR (< 10th percentile on twins’ growth charts): 18 with sIUGR and 16 with nsIUGR. The sIUGR group was made up of 18 pregnancies in which growth was restricted in only one fetus (n = 18). The nsIUGR group was composed of 8 pregnancies in which both fetuses presented restricted growth (n = 16). Cases of twin-to-twin transfusion syndrome and fetal malformation were not included in the study. Results: the MCDA twin pregnancies with sIUGR had a higher rate of orotracheal intubation (p = 0.001) and mechanical ventilation (p = 0.0006), as well as longer than average fasting time (p = 0.014) compared to those in which the fetuses had nsIUGR. A higher incidence was also observed of types II and III umbilical artery Doppler velocimetry patterns in the sIUGR cases (p = 0.002). There was no significant difference between the two groups as to mortality during pregnancy and the neonatal period (p = 0.09). Conclusion: in MCDA twin pregnancies, sIUGR presents more severe umbilical artery Doppler velocimetry abnormalities and worse morbidity than nsIUGR.